The Establishing the Protocol for Genotyping SNPs rs1057910 in CYP2C9 and rs9923231, rs9934438 in VKORC1 genes Derived from Blood Samples of Cardiac Valve Replacement Patients Treated with Acenocoumarol - Thi Le Hang, Do; Nhung, Pham Thi Hong; Hieu, Nguyen Huu; Nga, Nguyen Thi; Long, Dinh Doan; Kien, Phạm Trung; Thơm, Vu Thi (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 34 No 2DO - 10.25073/2588-1132/vnumps.4122, 2018)
Abstract: Acenocoumarol is widely prescribed for patients with risk of thromboembolism in Vietnam. Several previous studies revealed that genetic polymorphisms of CYP2C9 and VKORC1 genes were the important genetic factors inducing a high-impact upon the response of acenocoumarol. Therefore, this study was aimed to establish a rapid and efficient protocol for genotyping SNPs of CYP2C9 and VKORC1 genes in Vietnamese cardiac valve replacement patients treated with acenocoumarol. The protocol consisted of DNA extraction from peripheral blood samples, polymerase chain reaction (PCR) for amplification of target genes, identifying the genotypes by either Sanger sequencing or restriction fragment length polymorphism PCR (PCR-RFLP). The protocol was established based on the identified optimal conditions to amplify targeted polymorphisms, i.e. rs1057910 in CYP2C9 gene and rs9923231, rs9934438 in VKORC1 gene. Keywords: CYP2C9 gene , VKORC1 gene, acenocoumarol, DNA sequencing, PCR-RFLP. References: [1] A.J. Camm, Focused update of the ESC Guidelines for the management of atrial fibrillation: an update of the 2010 ESC Guidelines for the management of atrial. fibrillation. Developed with the special contribution of the European Heart Rhythm Association, Euro Heart 33 (2012) 2719-47. [2] J.C Sun, D.M., A. Lamy, Antithrombotic management of patients with prosthetic heart valves: current evidence and future trends, Lancet 374 (2009) 565–76. [3] R.G. Hart, P.L.v.A.M, Meta-analysis: antithrombotic therapy to prevent stroke in patients who have nonvalvular atrial fibrillation. Ann Intern Med 146 (2007) 857-67. [4] T.L. Verhoef, Long-term anticoagulant effects of the CYP2C9 and VKORC1 genotypes in acenocoumarol users. Journal of Thrombosis and Haemostasis 10 (2012) 606–614. [5] L. Bodin , C. Verstuyft , D.A. Tregouet et al, Cytochrome P450 2C9 (CYP2C9) and vitamin K epoxide reductase (VKORC1) genotypes as determinants of acenocoumarol sensitivity. Blood 106 (2005) 135–40. [6] M. Wadelius , L.Y. Chen, J.D. Lindh et al, The largest prospective warfarin-treated cohort supports genetic forecasting. Blood 113 (2009) 784–92. [7] M. Teichert , M. Eijgelsheim , A.G Uitterlinden et al, Dependency of phenprocoumon dosage on polymorphisms in the VKORC1, CYP2C9, and CYP4F2 genes. Pharmacogenet Genomics 21 (2011) 26–34. [8] M.S. Wen, M.T.M. Lee, J.J. Chen et al, Prospective study of warfarin dosage requirements based on CYP2C9 and VKORC1 genotypes. Clin Pharmacol Ther 84(1) (2008) 83-89. [9] M.J. Drittij, H.H. Thijssen, V.L., J.C. de Vries-Hanje, Altered pharmacokinetics of R- and S-acenocoumarol in a subject heterozygous for CYP2C9*3, Clin Pharmacol Ther 70 (2001) 292-8. [10] G.J, T.G.M, Warfarin: what are the clinical implications of an outof-range-therapeutic International Normalized Ratio, Thrombolysis 27 (2009) 293-9. [11] PharmGKB [Internet]. Palo Alto (CA): Stanford University. Haplotype CYP2C9*3. [Cited 2012 Feb 22]. Available from: http://www.pharmgkb.org/haplotype/PA165816544, ngày truy cập 11/02/2018 [12] D.J. Harrington, G.R.H. et al, Pharmacodynamic resistance to warfarin is associated with nucleotide bstitutions in VKORC1, Haemost 6 (2008). [13] P.H. Reitsma, v.d.H.J., A.P. Groot et al, A C1173T dimorphism in the VKORC1 gene determines coumarin sensitivity and bleeding risk, PLoS Med 2 (2002). [14] A.D. Buzoianu, A.P. Trifa, D.F. Muresanu, S. Crisan, Analysis of CYP2C9*2, CYP2C9*3 and VKORC1 -1639 G>A polymorphism in a population from South-Eastern Europe, Journal of Cellular and Molecular Medicin 16 (12) (2012) 2919-2924. [15] Y.A. Chua, W.Z. Abdullah, Z. Yusof et al (2015), "VKORC1 and CYP2C9 genotypic data-based dose prediction alone does not accurately predict warfarin dose requirements in some Malaysian patients", Turk J Med Sci, 45(2), p. 913-8.